Innovative Capacities of Shipbuilding Organizations Manufacturing Composite Ships - Violeta Šugar; Josip Zanze (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
During the transitional period at the end of the 20th century, Croatian small composite shipbuilding (SCS) had merely 27 models. Still, at the end of the first decade of the 21st century, this innovative industry showed resilience and readiness to adapt to the new business conditions and created 237 basic models. The main goal of the research was the assessment of the innovative capacity of SCS in Croatia. The research was carried out via survey and interviews. It included 73 SCS organisations, based on the main hypothesis that there is a positive relationship between the innovative capacity and innovative appearances (innovative management, innovation culture, innovative policy, and innovative factors) as well as the performance of the organization. The testing was performed with the Pearson's correlation coefficient, the ANOVA and the post hoc LSD test resulted in the confirmation of the main and the three ancillary hypotheses. For the first time in Croatia, a new model of assessment of innovative capacities and innovative phenomena is presented, aiming to raise awareness of the need to strengthen the innovative capacities as a basis for the development of SCS.
Keywords: D02; O14; O31; O32; 330; small composite shipbuilding; innovative capacity; innovative management; innovation culture; innovative policy; innovative factors; innovation ecosystem; Croatia